Elder abuse the real definition : abusive verbal interactions. - Stevens, Georgia L.; University of Maryland at Baltimore. Video Press (Baltimore, Md. : Video Press, University of Maryland School of Medicine, 2000)
Five nurses discuss how to treat elderly long-term care patients with respect, and how important communication can be in preventing situations of verbal abuse of patients.
Presented by Georgia Stevens.
Keywords: Elder Abuse -- prevention & control; Aged; Communication; Long-Term Care -- methods; Nurse-Patient Relations